Graduate Student Conference in Russian Language and Literatures (Helsinki—Tallinn—Tartu) - Gushchin, Veniamin; Khalturin, Sergei (Slavica Revalensia, 2023)
This is an overview of a newly established series of Estonian-Finnish conferences on Russian language and literatures (russkaia filologiia). In 2023, this conference united graduate students from Croatia, Czechia, Estonia, Finland, Germany, Israel, Italy, Latvia, Poland, Switzerland, the US and Uzbekistan. The first conference of the series took place at Tallinn University from May 12 to 14, 2023, while the upcoming two conferences will be held in Tartu (2024) and Helsinki (2025).